Heritage-making and the Revival of Jhijhiya in Janakpurdham (Rigvedic Himalaya, 2024)
Jhijhiya is a dance performed by women and girls of the Maithil communities of India and Nepal. As part of a ritual practice, it is performed for Goddess Durga by specific castes only during the festival of Dashain, to ward off evil powers. As a folk dance, it is performed at any time of the year by cultural groups and it has become a much loved symbol of Maithil identity. Over the last decades, the practice of jhijhiya had declined. In some villages of Dhanusha district, the dance was dying out. Since 2018, urban youth and cultural organisations volunteered to revive the dance by organising public events inviting both jhjhiya teams from nearby villages and urban cultural groups. Around the same period, a grassroots organisation engaged women from marginalised communities, revived the dance in their villages, and also provided them with a platform to perform in Janakpurdham and from there in other communities of the area. Such a revival has spurred interest and led to the establishment of new jhijhjiya teams both in Janakpurdham and in villages around.Based on ethnographic research carried out in Dhanusha district between 2022 and 2024, this article aims first to locate jhijhiya as a ritual dance still practised in both urban and rural areas during Dashain. Second, it will explore how different Janakpurdham organisations are engaging with communities to revive jhijhiya and reposition it as a folk dance and an icon of Maithili heritage. Thirdly, this article will look at how the dance has changed in the process of heritagisation. In conclusion, I will argue that what jhijhiya is and how it should be practiced is still a contested issue but probably the shift from ritual to heritage has revitalised a dance that was previously considered on the verge of extinction.